2009
DOI: 10.1590/s0073-47212009000300011
|View full text |Cite
|
Sign up to set email alerts
|

The importance of dietary calcium consumption in two species of semi-terrestrial grapsoid crabs

Abstract: ABSTRACT. Calcium (Ca) is essential for crustaceans, due to calcium carbonate (CaCO 3 ) deposition in the new exoskeleton to harden it. The purpose of this work was to study short term Ca balance in terms of dietary Ca ingestion in two phylogenetically related crabs (Superfamily Grapsoidea) showing different degrees of terrestrial adaptations: Sesarma rectum Randall, 1840 and Neohelice granulata (Dana, 1851). Dietary Ca ingestion was studied using purified diets with different Ca concentrations (0, 2.2 and 6.6… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
5
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 47 publications
(40 reference statements)
1
5
0
Order By: Relevance
“…The nutritional value differs mainly in the content of calcium, nitrogen, and phosphorus (shrimp > squid > fish) [ 37 ] Calcium content in the diet can increase the growth efficiency of crabs, as shown in this study (Group 1 > Group 2 > Group 3) (*** p < 0.001). Our results showed the same growth response as in the Scylla serrata [ 38 ], Eriocheir sinensis ) [ 39 ], and superfamily Grapsoidea [ 40 ] species. Different diets with nutritional content rich in calcium can alter the frequency of molting and therefore promote the growth of crabs [ 41 ].…”
Section: Resultssupporting
confidence: 81%
“…The nutritional value differs mainly in the content of calcium, nitrogen, and phosphorus (shrimp > squid > fish) [ 37 ] Calcium content in the diet can increase the growth efficiency of crabs, as shown in this study (Group 1 > Group 2 > Group 3) (*** p < 0.001). Our results showed the same growth response as in the Scylla serrata [ 38 ], Eriocheir sinensis ) [ 39 ], and superfamily Grapsoidea [ 40 ] species. Different diets with nutritional content rich in calcium can alter the frequency of molting and therefore promote the growth of crabs [ 41 ].…”
Section: Resultssupporting
confidence: 81%
“…In intensive aquaculture, a large proportion of calcium is required to harden the new exoskeleton in crayfish (Zanotto et al . ). Calcium is stored in the exoskeleton and used when the crayfish undergoes moulting.…”
Section: Discussionmentioning
confidence: 97%
“…Due to the high amount of sand found in all the sampled crabs, we do not believe that this item is there by accident. Corroborating with Pires et al (2017), who stated that Ca, in the form of calcium carbonate, in addition to chitin and proteins, is the main constituent of the structure of the crustacean exoskeleton, and Nedzarek et al (2019) who claim that Ca and Mg are elements found in high concentration in the exoskeletons; Zanotto & Pinheiro (2009) pointed out that the crab Sesarma rectum excreted crystals of calcium carbonate (CaCO3), to the new exoskeleton, in direct proportion to the amount of calcium ingested.…”
Section: Discussionmentioning
confidence: 93%